2016
DOI: 10.3892/ijo.2016.3416
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine prevents metastasis of human osteosarcoma cells via S phase arrest and suppression of tumor-related neovascularization and osteolysis through the CXCR4-STAT3 pathway

Abstract: Abstract. Osteosarcoma is the most common primary malignant tumor of the bone. The long-term survivals continue to be unsatisfactory for patients with metastatic and recurrent disease. Metastasis is still a severe challenge in osteosarcoma treatment. Sinomenine, an alkaloid from traditional Chinese medicine, has been proved to possess potent antitumor and anti-invasion effect on various cancers. However, the effect of sinomenine on human osteosarcoma and the underlying mechanisms remains unknown. We report her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…For example, quercetin inhibited the IL-6/STAT3 signaling pathway and inhibited growth and migration of glioblastoma cells (46). Plumbagin downregulated cyclin D1 and VEGF expression through STAT3 regulation (47), and sinomenine inhibited the invasion and metastasis through inhibition of the CXCR4-STAT3 pathway (48). As observed in these studies, crocin ameliorated the expression of genes related to cell proliferation and invasion, as evidenced by decreased expression of cyclin D1, VEGF and CXCR4.…”
Section: Discussionmentioning
confidence: 52%
“…For example, quercetin inhibited the IL-6/STAT3 signaling pathway and inhibited growth and migration of glioblastoma cells (46). Plumbagin downregulated cyclin D1 and VEGF expression through STAT3 regulation (47), and sinomenine inhibited the invasion and metastasis through inhibition of the CXCR4-STAT3 pathway (48). As observed in these studies, crocin ameliorated the expression of genes related to cell proliferation and invasion, as evidenced by decreased expression of cyclin D1, VEGF and CXCR4.…”
Section: Discussionmentioning
confidence: 52%
“…20 Tumor metastasis involves a series of important processes including tumor cells detach from the primary site, entry into the surrounding matrix, into the circulatory or lymphatic system, adherence to the endothelial cell wall and migration to the outside of the blood vessels, and angiogenesis and form new metastases. 21 To evaluate the biological effect of magnolol on osteosarcoma cells' migration, and invasion, we carried out wound healing and transwell invasion assay in vitro. Our results have shown that the migratory capability of MG-63 and 143B cells in magnolol-treated groups was weaker than that of the control group (Figure 2A and 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Herb-derived component is becoming increasingly important in tumor therapies. For example, curcumin, sinomenine and oldenlandia were all identified to be effective anti-osteosarcoma drugs (32)(33)(34). UA was identified in wax coating of apples 100 years ago.…”
Section: Discussionmentioning
confidence: 99%